COPD and Gut–Lung Axis: How Microbiota and Host Inflammasome Influence COPD and Related Therapeutics - Qu, Ling; Cheng, Qing; Wang, Yan; Mu, Hui; Zhang, Yunfeng (Frontiers in Microbiology, 2022)
The exact pathogenesis of chronic obstructive pulmonary disease (COPD) remains largely unknown. While current management strategies are effective at stabilizing the disease or relief the symptoms, new approaches are required to target underlying disease process and reverse lung function deterioration. Recent research showed that pneumonia bacteria is critical in disease progression and gut microbiome is likely perturbed in COPD, which is usually accompanied by a decreased intestinal microbial diversity and a disturbance in immune system, contributing to a chronic inflammation. The cross-talk between gut microbes and lungs, termed as the “gut-lung axis,” is known to impact immune response and homeostasis in the airway. Although the gut and respiratory microbiota exhibit compositional differences, the gut and lung showed similarities in the origin of epithelia of both gastrointestinal and respiratory tracts, the anatomical structure, and early-life microbial colonization. Evidence showed that respiratory infection might be prevented, or at least dampened by regulating gut microbial ecosystem; thus, a promising yet understudied area of COPD management is nutrition-based preventive strategies. COPD patient is often deficient in nutrient such as antioxidant, vitamins, and fiber intake. However, further larger-scale randomized clinical trials (RCTs) are required to establish the role of these nutrition-based diet in COPD management. In this review, we highlight the important and complex interaction of microbiota and immune response on gut-lung axis. Further research into the modification and improvement of the gut microbiota and new interventions through diet, probiotics, vitamins, and fecal microbiota transplantation is extreme critical to provide new preventive therapies for COPD.